Could BMP-2 and BMP-7 be biomarkers of coronary artery disease? A pilot clinical study - Saeed Nazemi; Atefeh Rezapour; Seyed Mohammad Hasan Moallem; Mohammad Afshar; Sepideh Elyasi; Elham Hashemi; Sheyda Golmohammadzadeh; Azadeh Zaerzadeh; Vahid Jomezadeh; Amir Hooshang Mohammadpour (Artery Research, 2018)
Background: Coronary artery calcification (CAC) is utilized as an important tool for the global risk assessment of cardiovascular events in individuals with intermediate risk. BMP-2 is a powerful inducer of bone formation and exposure to BMP-2 in the arteries leads to the loss of vascular smooth muscle cells (VSMC) markers and increase gene expression in favor of osteoblasts. BMP-7 is key factor in the bone and kidney and is suggested as inhibitor of vascular calcification. The main purpose of this clinical study was to find out the correlation between BMP-2 and BMP-7serum concentration and CAC in human for the first time. Methods: In this study 84 patients with coronary artery disease who fulfilled inclusion and exclusion criteria, entered the study. For all patients a questionnaire consisting demographic data and traditional cardiovascular risk factors were completed. CT-Angiography was carried out to determine coronary artery calcium score and ELISA method was used for measuring BMP-2 and BMP-7serum concentrations. Results: There was a significant positive correlation between BMP-2 serum concentration and total CAC score and also CAC of right coronary artery (RCA), left anterior descending (LAD), circumflex (CX), left main coronary artery (LMCA) (P < 0.05). Similar result was found for BMP-7 serum concentration except in LMCA (P > 0.05). Conclusion: Based on our results, we can suggest BMP-2 and BMP-7 serum concentration as a probable biomarker for coronary artery disease. However, more studies with higher sample size are necessary for its confirmation.